Urban, sub-urban or rural: where is the best place for electric vehicles?. (1st January 2014) - Newman, Daniel; Wells, Peter; Donovan, Ceri; Nieuwenhuis, Paul; Davies, Huw
This paper critiques the assumption that an urban setting is the most appropriate for electric vehicles. In so doing, it questions the implementation of transitions theory and socio-technical experiments in the quest to establish electric vehicles as an alternative to the existing automobility regime. For vehicle owners and infrastructure providers alike, as with society generally, the benefits of electric vehicles are maximised when usage is most intense; a difficult situation to achieve in urban areas aside from light commercial delivery and service applications. Using case study information from electric vehicle trials under the ENEVATE research programme into users of such vehicles in North West Europe, it is concluded that more policy and research attention should be given to sub-urban and rural electric vehicle applications as promising niches from which wider socio-technical change may develop.